The relationship between childhood maltreatment and child-to-parent violence and abuse - Liew, Shi Hui (2021)
Background: Child-to-parent violence and abuse continues to be largely understudied and poorly understood. This phenomenon refers to any non-fatal act(s), by a child, that causes physical, psychological, and/or financial harm to one’s parent(s). Several studies have explored the relationship between child-to-parent violence and abuse and childhood maltreatment. However, a consolidated understanding of this relationship is lacking. Research also tends to consider different types of abuse and neglect in isolation. Furthermore, the psychological mechanisms underlying the relationship remain largely theoretical. This thesis explored the relationship between five types of childhood maltreatment and three types of child-to-parent violence and abuse. Additionally, within these relationships, the explanatory roles of two symptoms of unresolved childhood maltreatment were clarified (i.e. trauma symptoms and cognitive distortions).